2020
DOI: 10.3390/f11121241
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Factors Influence Seasonal and Interannual Litterfall Production in a Tropical Dry Forest in Mexico

Abstract: Litterfall production plays a fundamental role in the dynamics and function of tropical forest ecosystems, as it supplies 70–80% of nutrients entering the soil. This process varies annually and seasonally, depending on multiple environmental factors. However, few studies spanning several years have addressed the combined effect of climate variables, successional age, topography, and vegetation structure in tropical dry forests. In this study, we evaluated monthly, seasonal, and annual litterfall production ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 89 publications
3
12
0
Order By: Relevance
“…Climatic variables such as temperature and precipitation are essential as they influence the annual litterfall production in forest ecosystems. A negative correlation was observed in the present study between the mean annual precipitation (mm) and mean litterfall (Mg/ha/y) which corroborates with the previous studies (Morffi-Mestre et al, 2020). Few studies in dry forests exhibited a close association between precipitation and litterfall .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Climatic variables such as temperature and precipitation are essential as they influence the annual litterfall production in forest ecosystems. A negative correlation was observed in the present study between the mean annual precipitation (mm) and mean litterfall (Mg/ha/y) which corroborates with the previous studies (Morffi-Mestre et al, 2020). Few studies in dry forests exhibited a close association between precipitation and litterfall .…”
Section: Discussionsupporting
confidence: 93%
“…Over the last few decades, there has been a rapid intrigue in the study of litterfall dynamics on various spatial scales (Souza et al, 2019) for numerous functions, i.e., to quantify nutrient dynamics (Zhu et al, 2019), energy security (Manolis et al, 2019), carbon and nutrient input (Feng et al, 2019), its contribution to net primary productivity (Chen et al, 2017), and in forest restoration (Lanuza et al, 2018). Various studies have been conducted on the litterfall dynamics in tropical forests, primarily in moist forests, with relatively few in dry tropical forests (TDFs) (Morffi-Mestre et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the amount of litter that accumulates on the soil varies greatly throughout the year because of the heterogeneity of species and local characteristics of climate and relief (MORFFI-MESTRE et al, 2020), the average litter values found in this study agree with those reported by Rocha (2006), who obtained annual values of accumulated biomass between 13.6 and 40.3 Mg ha -1 in a Submontane Dense Ombrophilous Forest, and by Caldeira et al (2008), who observed values from 4.5 to 5.3 Mg ha -1 in a forest remnant in the municipality of Blumenau, state of Santa Catarina, Brazil. The significant accumulation in the ML fraction, which represents material under the most advanced stage of fragmentation, but not in the humic form, suggests that total litter decomposition in these sites takes more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…Litter, which comprises mainly leaves and fragments that fall from trees and are deposited on the forest floor (DICK; SCHUMACHER, 2020), can be separated into fractions, and their analysis can assist in understanding biogeochemical cycling in forests. Characteristics of the litter deposited on the soil vary according to the abiotic and biotic conditions of the forest site, such as climatic factors, soil fertility, floristic composition, and successional stages (MORFFI-MESTRE et al, 2020). In addition, variations in litter accumulation on the ground indicate the local decomposition dynamic, and forest sites with greater litter accumulation tend to be environments where the decomposition process is incomplete (TANNER et al, 1998).…”
Section: Introductionmentioning
confidence: 99%